A Post‐Neoliberal European Order? Public Purpose and Private Accumulation in Green Industrial Policy. - Kampourakis, Ioannis (Modern Law Review, 2025)
This article examines the emerging legal rationalities of EU's green industrial policy, questioning if they represent a departure from the neoliberal paradigm that prioritised safeguarding the competitive order. I argue that the European Green Industrial Plan signals a new role for law in the orchestration and balancing of public purpose and private accumulation. This shift can be understood through a dual thesis of 'market instrumentalism' and 'political capitalism'. Market instrumentalism denotes the emergence of a regulatory regime that casts off value neutrality, seeking to shape markets in alignment with politically determined objectives. Political capitalism captures how public power politicises private accumulation, particularly through strategies of derisking that ensure private profitability while socialising investment risks. These two theses provide a framework to assess whether and to what extent elements of a post‐neoliberal European order are emerging. While the turn to market instrumentalism promises a demystification of markets, which are relegated from ends to means, the politicisation of private accumulation constrains this dynamic by conditioning instrumentalism on the preservation private profitability. The article concludes with a reflection on how the space opened by green industrial policy could be harnessed to democratise the political economy of the green transition.